Simulations of Structure Formation in the Universe: Hot vs Cold Dark Matter - Chover Lopez, Carlos (My University, 2010)
In the last century, new observational techniques and discoveries such as the Cosmic Microwave Background Radiation have brought a new dimension of knowledge about the Universe. Therefore new theories and models have been proposed to explain the observed Universe. Computer simulations are a very important tool because they lay a bridge between theory, often over-simplified, and observations, which reveal the complexity of our Universe. In this thesis, it is given a review of observations including the most important discoveries and results that help to describe the Universe and have been used to develop the models considered nowadays. The cosmological theory behind the large-scale structure formation is explained, from the basis of the Friedman model to the formation of structures through the linear, quasi-linear and non-linear regime, including the Zeldovich approximation and the spherical collapse model. Furthermore, the different types of codes used for cosmological simulations are introduced, focusing on the N-body codes and presenting the code used in this thesis, developed by Klypin and Holtzman (1997). The tools used to analyse the results: density plots, power spectrum and mass variance are described as well.
Keywords: Astronomi, astrofysik och kosmologi; Astronomy, Astrophysics and Cosmology